The Hate U Give’s Swear Words & Word Formation Processes Analysis - Hanna Levina Goei; Wiwiek Sundari (Universitas Muhammadiyah Semarang, 2023)
The Black characters in The Hate U Give novel like to use many swear words in order to express their feelings and emotions. This is a study which deals with word formation process. To analyze the word formation processes in both swear words and non-swear words are the purposes of this study. To help conducting this study, close reading and note taking are used to collect the data. This study found that there are two types of swear words frequently used by the Black characters. Also, Expletive Interjection is the most frequent type of swear words which means that using swear words is how the Black characters express their emotions and feelings in certain situations